Cyber Bullying in Online Teaching During COVID-19 Experiences of Female Educators in India - Chakraborty, Debjani; Garg, Chhavi (JOURNAL OF INDIAN EDUCATION, 2022)
The onset of the COVID-19 pandemic in March 2020 in India triggered a nationwide lockdown and the education system too took one of the largest hits with most institutions shifting to online mode of teaching, posing a variety of challenges. The challenges were spread across a wide area, ranging from basic facilities like stable, high-speed internet and mobile phones or laptops to the lack of prior experience in teaching online, creating a sense of pressure as India converted to almost a full-time online teaching system. This naturally triggered a series of incidents, often in forms of incident messages, online class disruptions and ‘misuse’ of the online learning mediums to create chaos by students who found a way to take mischief making to a whole new level, and resorting to bullying in the cyberspace. While a number of studies are focusing on the challenges faced by students and understanding cyber bullying amongst classmates, the only literature available from the teachers’ point of view is in media coverage of such incidents, making this research essential for understanding challenges faced by educators. Hence, this study makes an attempt to understand experience of female teachers especially in context of untoward incidents happening while online teaching. An online survey was conducted in the present study and it was found that female teachers are facing incidents, which to some extent can be termed as cyberbullying.